2017
DOI: 10.3390/ijms19010070
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Skin Barrier Repair Effects of Topical Application of Some Plant Oils

Abstract: Plant oils have been utilized for a variety of purposes throughout history, with their integration into foods, cosmetics, and pharmaceutical products. They are now being increasingly recognized for their effects on both skin diseases and the restoration of cutaneous homeostasis. This article briefly reviews the available data on biological influences of topical skin applications of some plant oils (olive oil, olive pomace oil, sunflower seed oil, coconut oil, safflower seed oil, argan oil, soybean oil, peanut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
338
0
39

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 473 publications
(383 citation statements)
references
References 134 publications
6
338
0
39
Order By: Relevance
“…This increases the level of serum IgE, which activates histamine-secreting mast cells. Another skin barrier-related hypothesis suggests that impaired functioning of the skin epidermal barrier critically influences the pathology and progression of AD [4]. Dysfunction of the skin barrier is associated with severe skin dehydration and changes in various genes/proteins related to the modulation of epidermal homeostasis, such as filaggrin and claudin 1 [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…This increases the level of serum IgE, which activates histamine-secreting mast cells. Another skin barrier-related hypothesis suggests that impaired functioning of the skin epidermal barrier critically influences the pathology and progression of AD [4]. Dysfunction of the skin barrier is associated with severe skin dehydration and changes in various genes/proteins related to the modulation of epidermal homeostasis, such as filaggrin and claudin 1 [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, phenolic components are potent antioxidants and exhibit beneficial effect on plasma lipoproteins, and lipid oxidation. Polyphenols exert also a potent effect on inflammation process and oil phenolics are now being increasingly recognised for their anti‐inflammatory and antioxidant effects on the skin …”
Section: Introductionmentioning
confidence: 99%
“…Tocopherols and tocotrienols are well known for their benefits for skin health. A recent study indicated that shea butter was a famous antioxidant and anti-inflammatory plant seed extract used in the cosmetic industry because of its high percentage of unsaponifiable compounds including tocopherols and phytosterols [13,14]. Rekik et al also reported that the positive effect of vitamin E and phytosterols on collagen synthesis and skin wound healing is because these compounds prevent the damaging effects of free radicals and ensure the stability and integrity of biological membranes [15].…”
Section: Introductionmentioning
confidence: 99%